Fracture characteristics of silicene nanosheet with a crack under tension estimated using molecular dynamics simulation. (May 2019) - Fang, Te-Hua; Shen, Chien-Yu; Fan, Yu-Cheng; Chang, Win-Jin
Abstract: By conducting molecular dynamics (MD) simulations, we investigated the fracture behavior of a silicene nanosheet that had a pre-existing crack and was subjected to tensile loading. The effects of the crack length and crack angle were also examined under different tensile strains at different temperatures of 0, 100, 200, 400, and 500 K. According to the simulation results, the ultimate stresses and the corresponding strains decreased as the temperature increased. At 0, 100, 200, 400, and 500 K, the ultimate stresses on the silicene nanosheet with a crack length L of 3 nm and crack angle θ of 0° were 10.2, 9.8, 8.8, 7.9, and 7.4 N/m, respectively, and the corresponding strains were 0.35, 0.32, 0.28, 0.23, and 0.22, respectively. This study is crucial for the future design and application of silicene-based devices. Highlights: We study the fracture behavior of a silicene nanosheet using molecular dynamics. The silicene nanosheet with a pre-existing crack is subjected to tensile loading. The effects of the crack length and crack angle were examined. The ultimate stresses decreased as the temperature increased.